GREEN HRM PRACTICES AND SUSTAINABLE PERFORMANCE: EXAMINING THE ROLE OF GREEN TRANSFORMATIONAL LEADERSHIP - S, Rosyidah Karimah; Suswati, Endang; Priyatna, Navi Muda (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.14.NO.02.TAHUN.2025DO - 10.24843/EEB.2025.v14.i02.p04, 2025)
This study examines the influence of green human resource management (GHRM) practices on sustainable performance, with green transformational leadership (GTL) as a mediating variable. Conducted at a brown sugarcane factory in Malang, the research addresses sustainability challenges in the manufacturing sector. Using a quantitative approach, data were collected from 172 employees through purposive random sampling and analyzed using Structural Equation Modeling (SEM) with SMART PLS. The results indicate that GHRM practices significantly enhance sustainable performance, particularly in environmental, social, and economic aspects. GTL strengthens the implementation of GHRM and directly contributes to improved sustainability outcomes. While GTL partially mediates the relationship between GHRM and sustainable performance, the direct impact of GHRM remains more dominant. This study provides novel insights into the mediating role of GTL in strengthening the link between GHRM practices and sustainable performance, particularly in the manufacturing sector . Managers should adopt GTL to foster an environmentally responsible culture, motivate employees, and improve performance. Policymakers are urged to integrate green HR and leadership practices, while companies should invest in green training, external collaborations, and eco-friendly technologies to boost sustainable performance.